2nd International Arctic Ungulate Conference - Anonymous, A. (Rangifer, 1996)
The 2nd International Arctic Ungulate Conference was held 13-17 August 1995 on the University of Alaska Fairbanks campus. The Institute of Arctic Biology and the Alaska Cooperative Fish and Wildlife Research Unit were responsible for organizing the conference with assistance from biologists with state and federal agencies and commercial organizations. David R. Klein was chair of the conference organizing committee. Over 200 people attended the conference, coming from 10 different countries. The United States, Canada, and Norway had the largest representation. The conference included invited lectures; panel discussions, and about 125 contributed papers. There were five technical sessions on Physiology and Body Condition; Habitat Relationships; Population Dynamics and Management; Behavior, Genetics and Evolution; and Reindeer and Muskox Husbandry. Three panel sessions discussed Comparative caribou management strategies; Management of introduced, reestablished, and expanding muskox populations; and Health risks in translocation of arctic ungulates. Invited lectures focused on the physiology and population dynamics of arctic ungulates; contaminants in food chains of arctic ungulates and lessons learned from the Chernobyl accident; and ecosystem level relationships of the Porcupine Caribou Herd.